Family Support in Caring for Cancer Patients During the Covid-19 Pandemic - Rizka Wahyu Utami; Sutantri Sutantri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The COVID-19 Pandemic period has a major impact on life, especially causing psychological problems for sensitive groups, namely the elderly and people who have chronic diseases such as cancer. Fear of infection, more severe complications, delays in diagnostics, treatment, and survival care put additional stress on cancer-affected patients. This raises concern for cancer patients that require support from various parties, especially families. Knowing the search for family support literature in treating cancer patients during the pandemic. Search articles using four databases: Ebsco, Proquest, PubMed, Science Director published from 2019 to 2021 with the keywords Family support, Cancer, Covid 19, Qualitative research. Search results from 4 databases found 391 articles of relevance to the topic, after article duplication and screening were carried out there 20 articles were entered at the full text review stage and eligibility based on inclusion and exclusion criteria so that 7 articles were obtained to be reviewed. The results of the study show that from 7 literatures it was found that there are several themes that influence families in providing support to cancer patients including socio-demography, health systems, public health, political and socio-cultural factors that can affect the level and trajectory of resilience, distress, and unmet needs in cancer patients during COVID-19. The need for support from various sources, especially families to strengthen the positive coping of cancer patients during the pandemic, both from the nuclear family, extended family, and other social support. Abstrak: Masa Pandemi COVID-19 berdampak besar bagi kehidupan, terutama menimbulkan masalah psikologis bagi kelompok sensitif yaitu lansia dan orang yang memiliki penyakit kronis seperti kanker. Ketakutan akan infeksi, komplikasi yang lebih parah, keterlambatan dalam diagnosis, pengobatan, dan perawatan kelangsungan hidup memberikan tekanan tambahan pada pasien yang terkena kanker. Hal ini menimbulkan keprihatinan bagi penderita kanker yang membutuhkan dukungan dari berbagai pihak terutama keluarga. Mengetahui penelusuran literatur dukungan keluarga dalam merawat pasien kanker di masa pandemi. Cari artikel menggunakan empat database: Ebsco, Proquest, PubMed, Science Director terbitan 2019 hingga 2021 dengan kata kunci Family support, Cancer, Covid 19, Qualitative research. Hasil pencarian dari 4 database ditemukan391 artikel relevan dengan topik, setelah dilakukan duplikasi artikel dan penyaringan terdapat 20 artikel yang masuk pada tahap full text review dan kelayakan berdasarkan kriteria inklusi dan eksklusi sehingga didapatkan 7 artikel untuk direview.Hasil penelitian menunjukkan bahwa dari 7 literatur ditemukan beberapa tema yang mempengaruhi keluarga dalam memberikan dukungan kepada pasien kanker diantaranya faktor sosial demografi, sistem kesehatan, kesehatan masyarakat, politik dan sosial budaya yang dapat mempengaruhi tingkat dan lintasan ketahanan, kesusahan, dan kebutuhan yang tidak terpenuhi pada pasien kanker selama COVID-19. Perlunya dukungan dari berbagai sumber terutama keluarga untuk memperkuat koping positif pasien kanker di masa pandemi, baik dari keluarga inti, keluarga besar, maupun dukungan sosial lainnya.